A Theranostic Agent Combining a Two‐Photon‐Absorbing Photosensitizer for Photodynamic Therapy and a Gadolinium(III) Complex for MRI Detection. Issue 8 (21st January 2016) - Schmitt, Julie; Heitz, Valérie; Sour, Angélique; Bolze, Frédéric; Kessler, Pascal; Flamigni, Lucia; Ventura, Barbara; Bonnet, Célia S.; Tóth, Éva
Abstract: The convergent synthesis and characterization of a potential theranostic agent, [DPP‐ZnP‐GdDOTA] −, which combines a diketopyrrolopyrrole‐porphyrin component DPP‐ZnP as a two‐photon photosensitizer for photodynamic therapy (PDT) with a gadolinium(III) DOTA complex as a magnetic resonance imaging probe, is presented. [DPP‐ZnP‐GdDOTA] − has a remarkably high longitudinal water proton relaxivity (19.94 mm −1 s −1 at 20 MHz and 25 °C) for a monohydrated molecular system of this size. The Nuclear Magnetic Relaxation Dispersion (NMRD) profile is characteristic of slow rotation, related to the extended and rigid aromatic units integrated in the molecule and to self‐aggregation occurring in aqueous solution. The two‐photon properties were examined and large two‐photon absorption cross‐sections around 1000 GM were determined between 910 and 940 nm in DCM with 1 % pyridine and in DMSO. Furthermore, the new conjugate was able to generate singlet oxygen, with quantum yield of 0.42 and 0.68 in DCM with 1 % pyridine and DMSO, respectively. Cellular studies were also performed. The [DPP‐ZnP‐GdDOTA] − conjugate demonstrated low dark toxicity and was able to induce high one‐photon and moderate two‐photon phototoxicity on cancer cells. Abstract : A bifunctional agent that combines a (diketopyrrolopyrrole)porphyrin component as a two‐photon photosensitizer for photodynamic therapy (PDT) with a gadolinium(III) DOTA complex as a magnetic resonance imaging probe was synthesized. Relaxometric, photophysical, and in cell studies highlight the potential of this molecule as a theranostic agent.